2021
DOI: 10.3390/catal11040428
|View full text |Cite
|
Sign up to set email alerts
|

Degradation Kinetics of Methyl Orange Dye in Water Using Trimetallic Fe/Cu/Ag Nanoparticles

Abstract: The release of azo dye contaminants from textile industries into the environment is an issue of major concern. Nanoscale zerovalent iron (nZVI) has been extensively studied in the degradation of azo dye pollutants such as methyl orange (MO). In this study, iron was coupled with copper and silver to make trimetallic Fe/Cu/Ag nanoparticles, in order to enhance the degradation of MO and increase reactivity of the catalyst by delaying the rate of oxidation of iron. The synthesis of the trimetallic nanoparticles (F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(28 citation statements)
references
References 65 publications
3
16
0
Order By: Relevance
“…It is observed that TOF has the same tendency as that of the adsorption capacity (q [µg•mg −1 ]); as the AuNPs concentration increases, the value of TOF is reduced. Again, these TOF values for dye degradation are consistent with values reported elsewhere for other nanoparticles [49,50].…”
Section: Resultssupporting
confidence: 91%
“…It is observed that TOF has the same tendency as that of the adsorption capacity (q [µg•mg −1 ]); as the AuNPs concentration increases, the value of TOF is reduced. Again, these TOF values for dye degradation are consistent with values reported elsewhere for other nanoparticles [49,50].…”
Section: Resultssupporting
confidence: 91%
“…Most synthetic dyes are soluble in water, thanks to the ionizable groups that compose them, such as: -OH, -COOH, and -SO 3 H in acid dyes, and -NH 2 , -NHR, and -NR 2 in basic dyes. It is estimated between 50% and 70% of the world production of 10,000 synthetic dyes (dyes and distinctive dyes used in the textile industry) corresponds to azo dyes, which represent the class of compounds most used in textile and food processes [ 10 , 11 ]. The pH value of the aqueous medium favors the ionization of the groups, depending on the pKa value of the chemical species in the solution.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, it is an allergenic substance that can cause eczema upon contact with the skin. Its presence in living organisms is considered harmful and can lead to a significant increase in the activity of the azo-nitro-reductase enzymes, producing aromatic amines that may cause intestinal cancer [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The TMNs exhibited 100% degradation efficiency inside 1 min, whereas, Fe/Cu and Fe/Ag showed 100% and 69% in 10 and 15 min, respectively. 185 In another study, Emam and Ahmed 186 synthesized homo-metallic (Ag) and hetero-metallic (Ag-Au) and Ag-Au-Pd nanostructures with sizes of 9.1, 23.7, and 13.6 nm, respectively, using sequential reduction. The nanostructures were used for the degradation of MB and MO in the presence of sodium borohydride.…”
Section: Environmental Applicationmentioning
confidence: 99%